THE EFFECT OF RECRUITMENT TECHNOLOGY ON EMPLOYEE SATISFACTION IN MARIST SECONDARY SCHOOLS IN NIGERIA. (Cuea Journal of Business and Economics, 2025)
This study aimed to examine the impact of the recruitment technology on staff satisfaction in the Marist Secondary Schools in Nigeria. The study was based on positivist research philosophy, which held to the idea that a direct observation and measurable phenomenon should be used as a source of knowledge. Positivism promotes objective research which is empirically oriented and that focuses on quantifiable data in order to disclose patterns and to examine associations (Creswell & Creswell, 2018). To reflect this paradigm, the researchers used the quantitative approach to the study to objectively determine the extent to which the recruitment tools employed into the process, like technology platforms of digital applicants, automated screening and online job boards, affect employee satisfaction in teaching personnel. The study adopted the Technology Acceptance Model (TAM) as the theoretical framework and concentrated on the perception of usefulness and easiness in the process of influencing the acceptance and use of technologic systems by people. The data set described came as a result of the administration of structured questionnaires to 223 respondents who were sampled after a target population of 502 employees on the 11 Marist Secondary Schools in Nigeria. An investigative research design that involved a combination of descriptive and explanatory research designs was used and the instrument used was validated through a pilot-test in two schools. Inferential statistical tools were used, which made it possible to study the relations between variables and provided reliability and generalizability of results according to the rules of positivism. The correlation study between the recruitment technology and the employee satisfaction was also reported as significantly positive (r = 0.533, p < 0.01). This discovery implies that the application of effective recruitment processes, including candidate selection using AI and shorted onboarding, has a positive effect on job fit, onboarding experience, and employee engagement in general. These technologies help in increasing the level of job satisfaction by enhancing perceived fairness, decreasing administrative bottleneck, and increasing the openness of the recruitment process. Following the insights, the research proposes that educational establishments, including Marist Secondary Schools and other establishments, invest in powerful HRM technologies, consider data-informed recruitment and reinforce the digital infrastructure, as well as encourage flexible work models. The results have significant implication to school administrators, HR practitioners, education policymakers, researchers, and faith-based education institutions trying to leverage technology to increase employee satisfaction and retention as a result of their technology-enhanced HR practices.